Strategi Penerapan Metode Menjodohkan Dalam Meningkatkan Kemampuan Memahami Sejarah Di Lingkungan Setempat Siswa Sekolah Dasar - HERLINA, HERLINA (Komunitas Manajemen Kompetitif, 2017)
Abstract: A history lesson in elementary school difficult given understanding to the students, for many reasons, such as the problem of learning methods. During use the lecture method, expected by the application of the method will match better understand the history of the student. Tidakan research method used in this study. Data collected by the test and observation and analyzed with descriptive analysis. The results showed that the change of improvement in student achievement. Through the application of the method pairing with giving cards as a form of review questions of clarification teacher in the classroom and students are asked to think of an answer and match with colleagues who have the same card it can be proved that the achievement of students of the thoroughness of 75 is increasing. Keywords: Matching Method, Historical Understanding Capabilities